2013
DOI: 10.1177/0361684313494357
|View full text |Cite
|
Sign up to set email alerts
|

Life History Models of Female Offending

Abstract: Our mixed-methods study advances understanding of pathways to offending for jailed women with and without mental illness. Life history interviews with 115 women from five U.S. states examined how onset of crime and delinquency varied based on mental health status and trauma exposure. Women in jails had high rates of mental health disorders, with a majority meeting lifetime diagnostic criteria for a serious mental illness (50%), posttraumatic stress disorder (51%), and/or substance use disorder (85%). Cox regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(72 citation statements)
references
References 46 publications
8
62
0
2
Order By: Relevance
“…Similar to other studies of justice-involved women (e.g., DeHart et al 2013), most women (75 %) experienced victimization as an adult; 65 % by partners and 43 % by non-partner others. Moreover, a four-region study of women in detention found that there are high rates of victimization by partners (77 %), caregivers (60 %) and others (63 %;DeHart et al 2013). It should be remembered that our measures did not include sexual violence.…”
Section: Victimization Histories As Critical Component For Understandsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar to other studies of justice-involved women (e.g., DeHart et al 2013), most women (75 %) experienced victimization as an adult; 65 % by partners and 43 % by non-partner others. Moreover, a four-region study of women in detention found that there are high rates of victimization by partners (77 %), caregivers (60 %) and others (63 %;DeHart et al 2013). It should be remembered that our measures did not include sexual violence.…”
Section: Victimization Histories As Critical Component For Understandsupporting
confidence: 81%
“…Moreover, a four-region study of women in detention found that there are high rates of victimization by partners (77 %), caregivers (60 %) and others (63 %;DeHart et al 2013). It should be remembered that our measures did not include sexual violence.…”
Section: Victimization Histories As Critical Component For Understandmentioning
confidence: 98%
“…Moreover, research demonstrates that substance use is related to victimization, as well as subsequent criminal justice involvement. (DeHart, Lynch, Belknap, Dass-Brailsford, & Green, 2014;Salisbury & vanVoorhis, 2009). Although we found no associations between relapse and recidivism in this study, our earlier research on the Beyond Violence RCT indicates that many incarcerated women have high rates of victimization, as well as symptoms of depression, anxiety, and PTSD (Kubiak et al, 2015); perhaps without treatment there might be a greater relationship between recidivism and relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Often, correctional staff members see individuals serving sentences only as perpetrators and not as victims of violence. For many justice-involved women, victimization histories begin at an early age and continue into adulthood (DeHart et al, 2014;Messina & Grella, 2006), and practices such as strip-searches and pat-downs may exacerbate trauma symptoms (Miller & Najavits, 2012;SAMHSA, 2013). Women's prisons that have implemented trauma-informed services have experienced substantial decreases in institutional violence (i.e., assaults on officers/other inmates) and mental health problems (e.g., decrease in suicide attempts; Benedict, 2014).…”
Section: Implications For Practicementioning
confidence: 99%
“…Kathleen Daly's (1992) Research has consistently found that women offenders report higher incidences of lifetime trauma, emotional problems, and mental health concerns than men prisoners and women in the general population (DeHart, Lynch, Belknap, Dass-Brailsford, & Green, 2014;Drapalski, Youman, Stuewig, & Tangney, 2009;Fazel & Seewald, 2012;Grella, Lovinger, & Warda, 2013). Some studies found victimization is associated with recidivism (Herbst, Branscomb-Burgess, Gelaude, Seth, Parker & Fogel, 2016;Taylor, 2015) and experiencing any trauma within the past year and history of physical abuse as an adult are significant predictors of recidivism (Bonta, Pang & Wallace-Capretta, 1995;Scott, Grella, Dennis & Funk, 2016).…”
Section: Deprivation and Importation Theorymentioning
confidence: 99%